Prevalence and practice for rare diseases in primary care: a national cross-sectional study in the USA. Issue 4 (1st April 2019) - Jo, Ara; Larson, Samantha; Carek, Peter; Peabody, Michael R; Peterson, Lars E; Mainous, Arch G
Abstract : Objectives: There are more than 7000 rare diseases in the USA, and they are prevalent in 8% of the population. Due to life-threatening risk and limited therapies, early detection and treatment are critical. The purpose of this study was to explore characteristics of visits for patients with rare diseases seen by primary care physicians (PCPs). Design: The study used a cross sectional study using a national representative dataset, the National Ambulatory Medical Care Survey for the years 2012–2014. Setting: Primary care setting. Participants: Visits to PCPs (n=22 306 representing 354 507 772 office visits to PCPs). Primary outcome measures: Prevalence of rare diseases in visits of PCPs was the primary outcome. Bivariate analyses and logistic regression analyses were used to compare patients with rare diseases and those without rare diseases and examined characteristics of PCP visits for rare diseases and practice pattern. Results: Among outpatient visits to PCPs, rare diseases account for 1.6% of the visits. The majority of patients with rare diseases were established patients (93.0%) and almost half (49.0%) were enrolled in public insurance programmes. The time spent in visits for rare diseases (22.4 min) and visits for more common diseases (21.3 min) was not significantly different (p=0.09). In an adjusted model controlling for patient characteristics (age, sex, types of insurance, reason for this visit, total number of chronic disease, having a rare disease and established or new patient), patients with rare diseases were 52% more likely to be referred to another provider (OR 1.52, 95% CI, 1.01 to 2.28). Conclusions: Visits for rare diseases are uncommon in primary care practice. Future research may help to explain whether this low level of management of rare diseases in primary care practice is consistent with a goal of a broad scope of care.